Development and Pharmaceutical Standardization of an Herbal Paste Containing Selected Ingredients from Varnya Dashakay - De Silva, C.S.; Senarathne, U.R.S.R.K. (Faculty of Indigenous Medicine, University of Colombo, 2025)
The increasing societal emphasis on beauty standards has led to a growing demand for cosmetic products, particularly skin complexion enhancers. The Ayurveda Acharya have identified and documented various herbal formulations regarding this concept. This research was aimed to develop and standardize an herbal paste containing selected ingredients from the Varnya dashakaya by Acharya Charaka for enhancing skin complexion. The inclusion criteria of the ingredients were the availability, feasibility and efficacy of the herbal ingredients towards skin disorders. The formulation was prepared according to the ‘Gandhaka malahara paribhasha’ presented in the authentic texts and standardized according to the methods prescribed in the Standard Operating Procedures by the Department of Ayurveda of Sri Lanka, the Indian Pharmacopoeia and World Health Organization. Standardization procedures included the evaluation of organoleptic parameters, spread-ability, homogeneity, qualitative phytochemical screening, determination of moisture content, Total Ash value, development of Thin Layer Chromatography (TLC) and High-Performance Thin Layer Chromatography (HPTLC) fingerprints. Phytochemical analysis revealed alkaloids, tannins, flavonoids and terpenoids indicating the developed formulation to consist of antioxidant, antimicrobial, antibacterial, antiviral, antifungal, anti-inflammatory and wound healing properties beneficial for the skin. The formulated paste demonstrated satisfactory physicochemical parameters including low mean values for moisture content (4.21%) and total ash content (4.16%) signifying its purity, stability and prolonged shelf life, while a pH range of 5-6 exhibiting its suitability as a skin application. Therefore, it can be concluded that, due to the combination of these properties, the formulated paste has the potential of being a multifunctional and effective skin care solution.
Keywords: Development and standardization; Herbal paste; Varnya dashakaya; Phytochemicals; Ayurveda